Pelatihan Pengelolaan Keuangan Bagi Ibu Rumah Tangga - Zikra Supri; Riyanti Riyanti; Nurhuda Nurhuda (Jurnal Abdimasa Pengabdian Masyarakat, 2023)
This activity aims to increase the understanding and knowledge of housewives in managing household finances properly so that there is no situation where expenditure is greater than income so that welfare is realized for the family. The method used in this activity is in the form of training or short training in managing household finances by using simple records. Participants are given training with activities by providing material and followed by a question and answer session and practice/practice; provision of simple bookkeeping filled in accordance with the real conditions of the participants. The activity participants were housewives in Rumaju Village totaling 15 people. The results of the study showed that the participants were very enthusiastic about participating in the activity from the beginning to the end of the activity. Besides that, based on the results of the Pre-Test and Post-Test, training participants can make their own financial accounting without the help of a resource person/instructor